Identifying with a Classically Liberal Nation: A Social Justice Perspective on Majority Opposition to Multiculturalism - Jessica Gale; Antoine Roblain; Christian Staerklé (International Review of Social Psychology)
Opposition to multiculturalism is common among native majorities. Normatively, this group-based political theory and public policy has been described as being incompatible with the individual justice-based orientation of Western liberal societies. In this research, we account for national majority opposition to multiculturalism by arguing that national identities in classically liberal societies are primarily associated with individual justice beliefs, in opposition to group-based justice beliefs. A correlational (N = 91) and an experimental (N = 172) study in Switzerland first show that the relationship between national identification and opposition to multiculturalism is partially explained by a belief in individual responsibility, a key facet of individual justice. This result was replicated using representative Swiss data from the World Values Survey (N = 1241), as well as in Belgium (N = 362), another Western liberal society. Effects transcended an ethnic conception of national identity and provide a novel perspective on majority multicultural attitudes as rooted in group-based conceptions of social justice.